2008
DOI: 10.3168/jds.2007-0804
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Breeding Protocols and Reproductive Tract Score on Reproductive Performance of Dairy Heifers and Economic Outcome of Breeding Programs

Abstract: The objectives of this study were to evaluate the effect of reproductive protocols and reproductive tract score on reproductive performance of dairy heifers and economic outcomes of breeding programs. Holstein heifers (n = 534), 13 +/- 1 mo of age, were randomly assigned to 1 of 4 reproductive protocols. On the day of enrollment (d 0), heifers were palpated per rectum and received a score according to the maturity of their reproductive tract (1 = prepubertal; 2 = peripubertal; and 3 = puber-tal). Estrous detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 29 publications
(48 reference statements)
3
36
2
Order By: Relevance
“…A limitation in our data, however, was that different inseminators were used for different parity groups, therefore confounding by inseminator cannot be excluded. In our data, days to calving during the second and subsequent calving seasons did not depend on days to calving of any of the preceding calving seasons (P > 0.05), in contrast to previous findings (Lesmeister et al, 1973, Pence et al, 2007, Stevenson et al, 2008, Cushman et al, 2013.…”
Section: Rts As Predictor Of Long-term Reproductive Performancecontrasting
confidence: 99%
See 3 more Smart Citations
“…A limitation in our data, however, was that different inseminators were used for different parity groups, therefore confounding by inseminator cannot be excluded. In our data, days to calving during the second and subsequent calving seasons did not depend on days to calving of any of the preceding calving seasons (P > 0.05), in contrast to previous findings (Lesmeister et al, 1973, Pence et al, 2007, Stevenson et al, 2008, Cushman et al, 2013.…”
Section: Rts As Predictor Of Long-term Reproductive Performancecontrasting
confidence: 99%
“…In this study RTS predicted the proportion of heifers pregnant and the time to pregnancy during the first breeding season, and to a lesser degree during the second breeding season (Table 4). Other researchers demonstrated that cows that calve early during the first calving season, calve early during subsequent seasons as well and have increased lifetime production (Lesmeister et al, 1973, MacGregor and Casey, 1999, Pence et al, 2007, Stevenson et al, 2008. In a previous report (Holm et al, 2009) we therefore hypothesised that heifers with higher RTS before the start of the first breeding season are likely to calve early during subsequent breeding seasons compared to their herd mates with lower RTS.…”
Section: Rts As Predictor Of Long-term Reproductive Performancementioning
confidence: 86%
See 2 more Smart Citations
“…The difference in the mean age at the first calving between the highest and lowest MY groups was 50 d (Table 1). Many studies suggest that the earlier the age at the first calving the better (Shamay et al 2005;Stevenson et al 2008). Krpálková et al (2014b) concluded that the lowest average milk yield in the lifetime production was observed in the age at the first calving higher than 24.5 months of age.…”
Section: High-producing Dairy Herdmentioning
confidence: 99%